Comparing crime types: a linguistic analysis of communiqués associated with the animal and earth liberation movement. Issue 2 (4th May 2019) - Logan, Michael K.; Hall, Margeret
ABSTRACT: The content and style of language reveal significant insight into psychological, cognitive, and emotional processes. A growing number of studies have also been devoted to linking language to psychological and social processes underlying violent extremism. Building on this body of literature, the current study examines the type of language used in communiqués associated with the earth and animal liberation movement between 2013 and 2017. We pay specific attention to differences in communiqués associated with different criminal events including arson, animal liberation, sabotage, and vandalism. We also compare the communiqué data to a collection of lone-actor terrorist's writings. The results suggest that communiqués linked to arson and animal liberation were highest on the indicators of affect and cognitive complexity compared to the other crime types. As a whole, the earth and animal liberation movement communiqués were similar to the lone-actor texts in negative emotions. Finding from this study support the influence of negative emotions, and anger in particular, in motivating and justifying violent extremism.